Managing hyperphosphatemia in patients with chronic kidney disease on dialysis with ferric citrate: latest evidence and clinical usefulness. (September 2015) - Yagil, Yoram; Fadem, Stephen Z.; Kant, Kotagal S.; Bhatt, Udayan; Sika, Mohammed; Lewis, Julia B.; Negoi, Dana
Ferric citrate is a novel phosphate binder that allows the simultaneous treatment of hyperphosphatemia and iron deficiency in patients being treated for end-stage renal disease with hemodialysis (HD). Multiple clinical trials in HD patients have uniformly and consistently demonstrated the efficacy of the drug in controlling hyperphosphatemia with a good safety profile, leading the US Food and Drug Administration in 2014 to approve its use for that indication. A concurrent beneficial effect, while using ferric citrate as a phosphate binder, is its salutary effect in HD patients with iron deficiency being treated with an erythropoietin-stimulating agent (ESA) in restoring iron that becomes available for reversing chronic kidney disease (CKD)-related anemia. Ferric citrate has also been shown in several studies to diminish the need for intravenous iron treatment and to reduce the requirement for ESA. Ferric citrate is thus a preferred phosphate binder that helps resolve CKD-related mineral bone disease and iron-deficiency anemia.